PERANCANGAN RUANG TERBUKA PUBLIK DI KECAMATAN PONTIANAK UTARA DENGAN PENDEKATAN DESAIN UNIVERSAL - Diartini, Livia; Andi, Uray Fery; Purnomo, Yudi (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2022)
The uneven distribution of the population in North Pontianak District has resulted in rapid development. This causes less attractiveness in the North Pontianak District area compared to other Pontianak City Districts. The limited infrastructure and public service facilities and the large number of people from children to the elderly with special needs led to the birth of a design idea that is able to answer all problems, namely by presenting a Public Open Space that accommodates community activities with a universal design approach (design for everyone). ). Universal design is a design concept that is intended for everyone regardless of differences. The design concept is applied to the design of products, the environment, and even a public open space that can facilitate the whole community. The purpose of designing public open spaces is to meet the needs of the people of North Pontianak District and its surroundings regardless of differences in background, culture, language, knowledge and level of physical ability. The method used is the design thinking method, which is a method that collects data and looks for solutions in a design. Design thinking is a method of solving problems for users (users). The Design of Public Open Spaces in North Pontianak District with a Universal Design Approach creates a public open space that applies seven (7) universal design principles. 7 universal design principles in the form of products, facilities and spaces designed based on the Universal design approach.